Text Ed.. Fernando Távora. «On board» Diary. Vol. 1. Diário de «bordo» - Marnoto, Rita (2012)
(2012. [Text Ed.]). Fernando Távora. «On board» Diary. Vol. 1. Diário de «bordo» (Coord. Álvaro Siza [Trad. Jane Considine & Tiago Esquível Faria]). Porto: Casa da Arquitectura, Fundação Instituto Arquitecto Marques da Silva [pp. 420]. ISBN 978 989 20 3394 5 Direitos de autor